Live reality television: Care structures within the production and reception of talent shows. (March 2019) - Hill, Annette; Askanius, Tina; Kondo, Koko
This article focuses on production and reception practices for live reality television using critical theory and empirical research to question how producers and audiences co-create and limit live experiences. The concept of care structures is used to make visible hidden labour in the creation of mood, in particular audiences as participants in the management of live experiences. In the case of Got to Dance, there was a play off between the value and meaning of the live events as a temporary experience captured by ratings and social media, and the more enduring collective-social experience of this reality series over time.